A nonconforming finite element method for fluid–structure interaction problems - Swim, E.W.; Seshaiyer, P. (Computer methods in applied mechanics and engineering, 2006)
In this paper, we develop a nonconforming finite element methodology using a three-field formulation to analyze a fluid–structure interaction problem. The methodology is used to couple a Lagrangian model describing the structure with the arbitrary Lagrangian–Eulerian strategy used to describe the fluid in order to simulate a full unsteady physical phenomenon. Consistency error estimates are obtained which show that the numerical scheme employed yields a first order approximation for the solution to the fluid–structure interaction problem. Finally, we present a discrete energy estimate to demonstrate the stablity of the proposed method.